EVALUASI TARGET DAN RENCANA KERJA KEGIATAN KADER MASYARAKAT DI DESA CIAPUS, KECAMATAN CIOMAS, KABUPATEN BOGOR - Rita Markus Idulfilastri; Fransisca Iriani R.D.; Cecilia Giwan Meilian (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2021)
PKM is a collaboration with Ambissi Association partners who have formed 23 cadres of Ciapus village. The activities are Health Services, Children's Reading Gardens, Savings and Loans, Medicinal Plant and Culinary Product. Problem analysis is related to the targets and work plans that have been made in the PKM of 2018-2019 period last semester. PKM problems now with the aim of seeing the realization of targets and work plans that have been made and to strengthen the understanding of cadres' self-evaluation of achievement thinking patterns. Due to the Covid-19 pandemic, activities were carried out by distributing a questionnaire